OUTSIDE COURT CONTROL OF THE WORK OF THE PUBLIC ADMINISTRATION –OMBUDSMAN (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
From the numerous legal competencies envisaged by the Law onOmbudsmen, this reserch focuses on the competence of exercisingcontrol over the legality, as well as the expediency of the undertakenactions and the decisions made by the employees in the public authortiesin the Republic of Macedonia (public administration). The aim of thisreserch is analysis of one segment, from the numerous competencies, andobservations of the activities undertaken by the Ombudsman as aninvestigator of the work of the public administration in the Republic ofMacedonia. The survey uses the method of analysis of the laws andsublaws, statistical indicators, as well as other relevant indicators thatindicate the role of the Ombudsman in the Republic of Macedonia as aninvestigator of the work of the public administration. The results of thesurvey portray the measures the Ombudsman has undertaken in it’s roleof performance in protecting human rights and freedoms when citizensare seeking services by the public administration.